Analysis of difficulties of japanese language study program students in determining learning media when field experience practice - Pangestika, Eva Meitha; Wardhana, Chevy Kusumah; Oesman, Andy Moorad (Chi'e: Journal of Japanese Learning and Teaching, 2018)
Learning media is anything that can be used to channel the message or the content of the lesson, stimulate the thoughts, feelings, attention and willingness of students so as to encourage the learning process. Therefore, as a teacher is expected to be skilled in determining learning media, as well as students of Japanese language education program Unnes who plays as a teacher in the implementation of Field Experience Practice. However, based on a preliminary study using a questionnaire distributed to students of the Japanese language education program class of 2011, 2012, 2013, the student still has difficulty in determining learning media such as powerpoint, e ka-do, jitsubutsu and so on.Therefore, the reseachers conducted a research. This study aims to determine the difficulty, causal factors and solutions in overcoming difficulties in determining learning media when PPL. The approach of this research is descriptive quantitative and qualitative. The sample of this study is a student of Japanese language education program unnes class of 2013 amounted to 52 students. Methods of data collection using questionnaires and the results obtained data were analyzed by descriptive technique percentage. Based on the results of research, can know the average percentage of answers obtained from the indicators of difficulty that is 37%. This shows that the students of the Japanese language education program class of 2013 have no difficulty in determining learning media when implementing PPL. That's because almost all students have made several efforts in overcoming the difficulty of determining learning media. Although students do not have difficulty in determining learning media when PPL, but there are two things to note is the technical quality of images on a media to fit the intent. In addition, student motivation conditions need to be considered when determining learning media. Media pembelajaran adalah segala sesuatu yang dapat digunakan untuk menyalurkan pesan atau isi pelajaran, merangsang pikiran, perasaan, perhatian dan kemauan siswa sehingga dapat mendorong proses pembelajaran. Oleh karena itu, Sebagai seorang guru diharapkan terampil dalam menentukan media pembelajaran, begitu pula mahasiswa prodi pendidikan bahasa Jepang Unnes yang berperan sebagai guru dalam pelaksanaan Praktik Pengalaman Lapangan. Namun, berdasarkan studi pendahuluan dengan menggunakan angket yang disebarkan kepada mahasiswa prodi pendidikan bahasa Jepang angkatan tahun 2011, 2012, 2013, mahasiswa tersebut masih mengalami kesulitan dalam menentukan media pembelajaran seperti powerpoint, e ka-do, jitsubutsu dan sebagainya. Oleh sebab itu, peneliti melakukan penelitian ini yang bertujuan untuk mengetahui kesulitan, faktor penyebab serta solusi dalam mengatasi kesulitan dalam menentukan media pembelajaran ketika PPL. Pendekatan penelitian ini adalah deskriptif kuantitatif dan kualitatif. Sampel penelitian ini adalah mahasiswa prodi pendidikan bahasa Jepang unnes angkatan tahun 2013 berjumlah 52 mahasiswa. Metode pengumpulan data menggunakan angket serta hasil data yang diperoleh dianalisis dengan teknik deskriptif prosentase. Berdasarkan hasil penelitian, dapat diketahui rata-rata perolehan prosentase jawaban dari indikator kesulitan yaitu 37%. Hal tersebut menunjukkan bahwa mahasiswa prodi pendidikan bahasa Jepang angkatan tahun 2013 tidak mengalami kesulitan dalam menentukan media pembelajaran ketika melaksanakan PPL. Hal itu dikarenakann hampir seluruh mahasiswa telah melakukan beberapa upaya dalam mengatasi kesulitan menentukan media pembelajaran. Meskipun mahasiswa tidak mengalami kesulitan dalam menentukan media pembelajaran ketika PPL, namun terdapat 2 hal yang perlu diperhatikan yaitu kualitas teknis gambar pada suatu media agar sesuai dengan maksud. Selain itu, kondisi motivasi siswa perlu dipertimbangkan ketika menentukan media pembelajaran